Preventive Patterns of Housewives in Preventing Anxiety as the Impact of Watching Television Movie - Nasution, Nurhasanah; Basit, Lutfi; Ginting, Rahmanita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
During the COVID-19 pandemic, watching television is an alternative choice for entertainment at home. Because activities outside the home are limited. One of the entertainments that are requested by women is television films or soap operas completed in one run. The television film that has the highest rating is "Voice of the Wife's Heart" which is currently airing on the Indosiar television station. Housewives or career women who work at home (work from home) really like the one-off soap opera, Suara Hati Istri (SHI). Stories that contain the concerns of women, especially housewives, have managed to attract attention, so the show has a high rating. Television films or so-called soap operas, which air every day on the Indosiar television station, raise conflicts and problems in the household. The specific purpose of this research is to see how the preventive pattern of housewives in preventing anxiety as a result of watching television movies. In determining the sample, which is used in this study is "Multistage Random Sampling". The sample selection technique uses the Slovin formula approach. The number of samples in this study was 400 people. The subject of this study involved housewives who had watched soap operas the voice of their wives' hearts for the past 1 year. The results showed that the preventive pattern of housewives in preventing anxiety as a result of watching television can be seen from several aspects. First, the participation of children in watching this program, children are not allowed to watch. This can result in children being able to imitate scenes both messages and behavior seen on the Suara Hati Istri FTV program, both contents were delivered by the actor on the Suara Hati Istri FTV broadcast. This can have a negative effect on family life. This requires educational education in preventing anxiety caused by broadcast programs.